Knowledge, perceptions and practices of menstrual hygiene among degree college students in Guntur city of Andhra Pradesh, India - Balla, Christina Patricia; Nallapu, Samson Sanjeeva Rao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The unmet menstrual hygiene needs of young girls in India restrict their mobility and daily activities. Taboos and socio-cultural restrictions contribute to poor knowledge and practices leading to adverse health outcomes. This study is set to look at the knowledge, perceptions and practices concerning menstruation among college going girls. Methods: This study was conducted with 254-degree college students from a women’s degree college in Guntur city. After assuring adequate confidentiality, a self-administered questionnaire was administered to each participant. The information obtained was entered and analysed in MS excel. Important findings were subjected to statistical tests like Chi square and Z test for significance testing at 5% LOS. Results: Mother’s education was significantly related to the girls’ knowledge about menses (2 16.6, p 0.00002). A positive perception of menses was associated with good knowledge about it. (p < 0.00001). Complaints related to menses were also associated with good knowledge scores (2 9.8, p 0.002). Absenteeism during periods was 81.5%, the causes being pain 60.4%, heavy bleeding 31.4%, both pain and heavy bleeding 4.8% and nausea 3.4%. Conclusions: The associated symptoms of menstruation need to be addressed in schools and colleges and in their respective homes. Ensuring availability of sanitary products, water, privacy and appropriate waste disposal in all public services and institutions can address the challenges.